KONFLIK LINGKUNGAN DI BUKIT MANGUNHARJO TEMBALANG: ANTARA KEPENTINGAN EKONOMI DENGAN KEPENTINGAN LINGKUNGAN - SUPRATIWI, SUPRATIWI (Program Magister Ilmu Politik, Universitas Diponegoro, 2013)
Abstract The research was motivated by the further degradation of the environment. Many of the pollution of water, air, landslides, floods, and so on. These conditions tend to increase in the era of regional autonomy. This is due to each province trying to get as much revenue from natural resources. Exploitation is carried out without offset to the maintenance and preservation. The result is environmental degradation that often lead to conflict. As it happens hill districts Mangunharjo Tembalang city of Semarang. C mining excavation at the site has a conflict of interest. Because of this formulation of the problem in this study was to determine why there is a conflict in the hill Mangunharjo; what causes it. The method used in this study was descriptive with qualitative data collection techniques through observation, interviews, and literature review. The results showed that the mineral mining activities in the hill Mangunharjo c positive and negative impacts. The positive impact of the perceived economic benefits a small portion of society. While the negative impact of environmental degradation is felt most of the people and Government of Semarang City. Caused by mining environment becomes damaged, but the area is a region Tembalang conservation. Frequent flooding, landslides, pollution, and so on. This is exactly what caused the conflict. The conflict has lasted several years and has not been resolved. Contributing factor is the vagueness and lack of regulation, weak law enforcement (government indecision), and lack of public awareness about the importance of theenvironment. Keywords: Conflict,Â Economics Interests, Environmental Interests